"The bottom line is that it is all about trust": Interviews with Health Services Administrators about perceived barriers and facilitators to vaccine administration in jails. Issue 1 (23rd January 2023) - Cassarino, Nicole; Lodolo, Laura; Smyth, Emma; Ramaswamy, Megha; Wurcel, Alysse
Abstract: Background: Compared to the general population, individuals incarcerated in jails and prisons are more vulnerable to infection and mortality from communicable diseases, such as COVID-19 and influenza. However, vaccination rates among incarcerated individuals as well as staff who work in jails and prisons remain disproportionately low. Healthcare administrators working in jails have first-hand experience about barriers to vaccine provision, but their perspectives are infrequently collected and analyzed. Methods: We reached out to Health Services Administrators (HSAs) from all 14 Massachusetts (MA) county jails for qualitative in-depth interviews to understand how their personal and professional feelings about vaccination relate to the barriers and facilitators that surround administration of vaccines in jail. Results: Eight people participated in the study (8/14 = 57% response rate). Key themes emerged, including 1) HSAs expressed divergent opinions on incarceration as the correct opportunity to vaccinate individuals, 2) HSAs' personal views on vaccines influenced their operationalization of vaccination in jail, and 3) opinions varied on whether their institutions' vaccine protocols needed modification. Conclusions: Our findings highlight the critical need to leverage the feedback and influence of stakeholders such as HSAs in efforts to improve preventative healthcare delivery in carceral health systems.